Factors influencing generation Y's purchase intentions of prototypical versus me-too brands - Quintal, V.; Phau, I.; Sims, D.; Cheah, Isaac (Pergamon, 2016)
© 2016 Elsevier Ltd. The current study examines self-confidence, perceived quality, extrinsic attributes and perceived risk as drivers and inhibitors of Generation Y's purchase intentions of prototypical and me-too brands. A survey of 348 respondents demonstrated that self-confidence and perceived quality produced significant positive effects on purchase intentions for the me-too brands. Extrinsic attributes produced a significant positive effect on purchase intentions for the prototypical brand. Perceived financial/performance risk produced a significant negative effect on purchase intentions for both the prototypical and me-too brands, while perceived psychological risk produced a significant negative effect on purchase intentions for the prototypical brand. Understanding the factors underlying Gen Y's consumer behaviour is crucial, particularly due to their considerable consumption potential and the increasing sophistication of brand marketing in the marketplace.